2016
DOI: 10.4103/0019-5278.183832
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of occupational radiation exposure among medical staff in health-care facilities in the Eastern Province, Kingdom of Saudi Arabia

Abstract: Introduction:Radiation exposure poses hazards for health-care providers as well as patients in health-care facilities (HCFs). Radiographic imaging is extremely valuable as a diagnostic tool in medicine, but ionizing radiation and computed tomography (CT) scan carry well-known potential risks. Personnel and radiation safety monitoring is an important safety precaution in the practice of radiography.Aim:The study aimed to assess the occupational radiation exposure and safety protection among medical staff in HCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 12 publications
(13 reference statements)
1
15
0
Order By: Relevance
“…Today, due to social factors such as the current medical environment and doctor-patient relationship, Chinese health care workers are under great pressure [24] and face the risk of experiencing serious injuries resulting from occupational exposure. Previous research on occupational exposure mostly focuses on the impact of specific substances or the behavior of health care workers [25, 26]. Few studies examine the current elements of occupational exposure and risk factors for health care workers, and none explore occupational exposure in relation to pediatric health care workers [2729].…”
Section: Introductionmentioning
confidence: 99%
“…Today, due to social factors such as the current medical environment and doctor-patient relationship, Chinese health care workers are under great pressure [24] and face the risk of experiencing serious injuries resulting from occupational exposure. Previous research on occupational exposure mostly focuses on the impact of specific substances or the behavior of health care workers [25, 26]. Few studies examine the current elements of occupational exposure and risk factors for health care workers, and none explore occupational exposure in relation to pediatric health care workers [2729].…”
Section: Introductionmentioning
confidence: 99%
“…Open Access: e-Journal always used lead aprons, 3.3% (n = 5) used lead goggles, 29.1% (n = 44) used thyroid shield, 2% (n = 3) used lead gloves and 21.2% (n = 32) used gonad shield as opposed with another study in Eastern Province, Saudi Arabia involving medical staff in health care facilities which reported 99% of medical staff always used lead aprons, 60% used a lead shield, 37% used lead glasses, and 42% used thyroid shield (K. Salama et al, 2016). However, findings in our study is better than other study in Northern Nigeria which reported 10.9% (n = 12) of respondent always used lead aprons, 4.5% (n = 5) used lead goggles, 2.7% (n = 3) used thyroid shield, 4.5% (n = 5) used lead gloves and 4.5% (n = 5) used gonad shield (Awosan et al, 2016).…”
Section: Ijphcsmentioning
confidence: 96%
“…Radiography (also called radiologic technology) includes conventional x-ray imaging as well as additional imaging modalities such as fluoroscopy, mammography, ultrasound (US), computed tomography (CT), magnetic resonance imaging (MRI), nuclear medicines (NM) and radiation therapy (RT). Radiography is an essential diagnostic tool of modern medicine.Within a hospital, radiologists, radiology and nuclear medicine technicians, and others involved in the performance of x-ray and computed tomography (CT)scan examinations, have an increased risk for radiation exposure than the general hospital population ( Salama, et al, 2016).…”
mentioning
confidence: 99%
“…The use of ionizing radiations in medicine is expanding rapidly due to the introduction of new ionizing radiation oriented diagnostic and therapeutic practices. Radiographic imaging is extremely valuable as a diagnostic tool in medicine, but ionizing radiation also carries well-known potential risks (Salama, et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation